معايير اختيار القائمين على أنشطة السياحة الترويحية بالاتحاد المصري للترياثلون - الشبكشي، آمنة مصطفى محمد; عبدالخالق، يحيى محمد الجيوشي; إبراهيم، أحمد عمرو Ibrahim, Ahmed Amr (جامعة حلوان - كلية التربية الرياضية للبنين, 2021)
First, the aim of the research: - The research aims to identify the criteria for selecting those in charge of recreational tourism activities for the Egyptian Triathlon Federation? Second: Research Questions: What are the criteria for selecting those responsible for the recreational tourism activities of the Egyptian Triathlon Federation. The researchers used the descriptive approach for its relevance to the nature of the study, and the research community included the research community, sports management and sports tourism experts, trainers, administrators, workers and pioneers in the Egyptian Triathlon Federation, and the number of the research community reached (170) individuals. The researchers chose the research sample from experts in sports management and sports tourism in the union Al-Masry Triathlon by the intentional method, while the researchers chose for the beneficiaries (players - coaches - referees - administrators) in a random way so that they are representative of the research community and one of the most important results he reached was that the behavioral standards have the ability to solve problems And they have a calm temper."
أولا: هدف البحث: - يهدف البحث إلى التعرف على معايير اختيار القائمين على أنشطة السياحة الترويحية الاتحاد المصري للترياثلون؟ ثانيا: تساؤلات البحث: -ما هي معايير اختيار القائمين على أنشطة السياحة الترويحية الاتحاد المصري للترياثلون؟ استخدم الباحثين المنهج الوصفي لمناسبته لطبيعة الدراسة، وشمل مجتمع البحث مجتمع البحث خبراء الإدارة الرياضية والسياحة الرياضية المدربين والإداريين والعاملين والرواد بالاتحاد المصري للترياثلون، وبلغ عدد حجم مجتمع البحث (170) فرد، قام الباحثين باختيار عينة البحث من خبراء خبراء الإدارة الرياضية والسياحة الرياضية بالاتحاد المصري للترياثلون بالطريقة العمدية بينما اختار الباحثين بالنسبة للمستفيدين (اللاعبين-المدربين-الحكام-الإداريين) بالطريقة العشوائية بحيث تكون ممثلة لمجتمع البحث وكانت من أهم النتائج التي توصل إليها أن المعايير السلوكية هناك قدرة على حل المشكلات. ولديهم هدوء الطبع."
Keywords: السياحة الرياضية -- السياحة الترويحية -- التربية الرياضية -- الأنشطة الرياضية -- الترويح الرياضي